A Review of Reagents for Fluorescence Microscopy of Cellular Compartments and Structures, Part III: Reagents for Actin, Tubulin, Cellular Membranes, and Whole Cell and Cytoplasm. Issue 1 (16th February 2018) - Kilgore, Jason A.; Dolman, Nick J.; Davidson, Michael W.
Abstract: Non‐antibody commercial fluorescent reagents for imaging of cytoskeletal structures have been limited primarily to tubulin and actin, with the main factor in choice based mainly on whether cells are live or fixed and permeabilized. A wider range of options exist for cell membrane dyes, and the choice of reagent primarily depends on the preferred localization in the cell (i.e., all membranes or only the plasma membrane) and usage (i.e., whether the protocol involves fixation and permeabilization). For whole‐cell or cytoplasmic imaging, the choice of reagent is determined mostly by the length of time that the cells need to be visualized (hours or days) and by fixation status. Presented here is a discussion on choosing commercially available reagents for these cellular structures, with an emphasis on use for microscopic imaging, with a featured reagent for each structure, a recommended protocol, troubleshooting guide, and example image. Curr. Protoc. Cytom . 67:12:32.1‐12:32.17. © 2014 by John Wiley & Sons, Inc.